Increased Levels of CD107a and Intracellular Cytokines in IL-2 Stimulated PBMCs from Endometriosis Patients - R. Muharam; Ririn Rahmala Febri; Kevin Ardito Prabowo; Arleni Bustami; Indra G. Mansur (Hindawi Limited, 2021)
It has been postulated that the immune system is impaired in individuals with endometriosis, with attention directed to natural killer (NK) cells. Specifically, it has been hypothesized that altered numbers of peripheral NK cells in blood are associated with the presence of endometriotic lesions. This study aimed to evaluate the level of the peripheral NK cell surface marker CD107a in endometriosis in the presence of IL-2 stimulation. Peripheral blood mononuclear cells (PBMCs) were obtained from 7 women with endometriosis and 7 women without endometriosis. The PBMCs were divided into two groups and either treated with recombinant IL-2 or left untreated. The cytotoxic activity of the PBMCs toward target cells (K562) was evaluated. Then, both groups were cocultured for 4 days. The expressions of CD107a, TNF-α, and IFN-γ were determined using flow cytometry analysis. There was no difference in the expression of CD107a prior to IL-2 stimulation in PBMCs from women with endometriosis compared to those from women without endometriosis. However, we observed upregulation of the expression of the surface marker CD107a after treatment in the endometriosis group. In addition, there was a significant difference in CD107a expression in the endometriosis group before versus after stimulation with IL-2 (p < 0.01). We also found no difference in the production of TNF-α and IFN-γ before versus after treatment with IL-2 in either groups. The levels of CD107a were significantly enhanced in peripheral blood taken from women with endometriosis after treatment with IL-2.